IR Based Auto-Recharging System for Autonomous Mobile Robot - Rao, M.V.Sreenivas; Shivakumar, M. (Journal of Robotics and Control (JRC), 2021)
As autonomous mobile robots are progressively utilized for appropriated missions, a significant issue that should be tackled is the autonomous recharging problem. The robots can be recharged by planning and arranging effectively to maximize its working efficiency. This paper presents the implementation of automatic docking robot with docking strategy and recharging capabilities. The robot is programmed using an algorithm which will guide the robot to move around in a square path of 30 inch by 30 inch continuously. While the robot is performing its assigned task, the battery remaining voltage is monitored by voltage detection module. When the battery voltage reaches threshold value of less than 12V, the microcontroller commands the robot to go back to the docking station for recharging autonomously. This system uses IR receiver sensor in front of the robot and IR transmitter sensor near docking station. The active IR transmitter sensor which transmit infrared signal located near docking area serves as landmark in guiding robot towards docking area. The robot scans the transmitted IR signal from the sensor transmitter only when it needs to charge its battery, if detected it will take the path of charging station. Once the robot approaches the charging station with the required orientation, it connects to the supply terminals for charging. The data related to battery charging voltage is transmitted by microcontroller through Bluetooth HC-05 to PLX DAQ software tool in PC stores it in the Excel sheet as the data arrive. Once the battery is fully charged the robot moves back to continue its original task.